Local institutions, actors, and natural resource governance in Kgalagadi Transfrontier Park and surrounds, South Africa. (September 2015) - Thondhlana, Gladman; Shackleton, Sheona; Blignaut, James
Highlights: The interplay of local institutions, actors and collaborative governance was examined. Lack of participation in decision-making, transparency and accountability undermine collaborative governance. Community heterogeneity and unequal access to benefits are central to conflicts. Re (configuration) of institutions is needed to reflect different actors' interests. Abstract: Crafting local institutions to allow more effective decision-making in the management of and access to natural resources in and beyond parks has long been considered key to collaborative governance. South Africa, in particular, has vigorously pursued collaborative governance as a desired approach to managing natural resources as evident in the new arrangements for previously restricted parks. However, though the discourse of collaborative governance has occupied conservation thinking and practice globally, few studies have looked at the interplay between local institutions, actors and collaborative governance involving indigenous hunter–gatherer communities in Southern Africa. In response, we assess the local actors and institutions that were put in place to facilitate collaborative governance of natural resources in the Kgalagadi Transfrontier Park and its surrounds in South Africa. Our findings show that though collaborative governance has a practical appeal, it is hampered by lack of participation in decision-making, information dissemination, transparency, trust and accountability, power relations, divergent interests and unequal access to natural resources. The findings also draw our attention to issues of heterogeneity, even within indigenous communities assumed to be homogenous by local conservation authorities as reflected in land settlement agreements in co-managed parks. We argue that collaborative governance arrangements need to reflect and be understood within the broader background of complex local realities.